2017
DOI: 10.1007/s10068-017-0191-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibiotic resistance phenotypes in laboratory strains and clinical isolates of Staphylococcus aureus, Salmonella Typhimurium, and Klebsiella pneumoniae

Abstract: This study was designed to evaluate the antibiotic resistance phenotypes in wild-type (WT-SA), oxacillin-induced (OI-SA), clinically-acquired antibiotic-resistant (CA-SA), wild-type Typhimurium (WT-ST), ciprofloxacin-induced . Typhimurium (CI-ST), clinically-acquired antibiotic-resistant. Typhimurium (CA-ST), wild-type (WT-KP), ciprofloxacin-induced (CI-KP), and clinically-acquired antibiotic-resistant (CA-KP). The resistance of WT-SA, WT-ST, and WT-KP to ampicillin, ceftazidime, and cephalotin, penicillin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In recent years, antibiotics have been used to treat diseasecausing bacteria. Antimicrobial resistance is a global threat to public health [1][2][3]. Enzymatic modification (b-lactamases), reduced permeability (selective blockage), increased membrane transport (efflux pumps), altered binding site (specific receptors) and metabolic bypass are the mechanisms of antibiotic resistance in bacteria [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, antibiotics have been used to treat diseasecausing bacteria. Antimicrobial resistance is a global threat to public health [1][2][3]. Enzymatic modification (b-lactamases), reduced permeability (selective blockage), increased membrane transport (efflux pumps), altered binding site (specific receptors) and metabolic bypass are the mechanisms of antibiotic resistance in bacteria [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Jo et al [ 29 ] demonstrated that in cancer patients, antimicrobial resistance in K. pneumoniae is linked to misuse and/or overuse of chemotherapeutic agents. Due to a decreased immunity in individuals undergoing antineoplastic chemotherapy, opportunistic pathogens such as K. pneumoniae can cause a wide range of infections, including pneumonia, urinary tract infection, bacteremia and meningitis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%